Tracking the Changes in Synchrony of the Electrophysiological Activity as the Uterus Approaches Labor Using Magnetomyographic Technique. (May 2015) - Govindan, Rathinaswamy B.; Siegel, Eric; Mckelvey, Samantha; Murphy, Pam; Lowery, Curtis L.; Eswaran, Hari
The objective of the study was to perform serial magnetomyographic examinations in order to detect changes in synchrony characteristics of myometrial electrophysiological activity as women approach labor. Of the total of 56 patients recruited, the results of 149 examinations from 29 patients were included in the analysis. The global synchrony across each sensor spread over the abdomen was computed and quantified as synchronization index. The mean and the median value of the global synchrony were computed and correlated with time to active labor from the last recording. Overall, synchrony increased as the patient approached active labor ( P = .035). Furthermore, mean synchronization index increased twice as fast in the nonnulliparous group compared to the nulliparous group ( P = .039). The changes in synchrony of uterine electrophysiological activity near term could aid in prediction of labor.